Microbiological quality of fruit pulp in Brazil: An overview of the years 2010 through 2020 (Research, Society and Development, 2021)
This review provides an overview of the microbiological quality of fruit pulps marketed in Brazil, through an integrative review of studies published between the years 2010 and 2020. Three databases were consulted (Academic Google, Scientific Electronic Library Online and Biblioteca Virtual Health), using the descriptors: fruit pulp, quality, microbiological quality and hygienic-sanitary quality. The search results were evaluated and selected, considering the objective of the study, as well as the inclusion and exclusion factors. The total of the 56 studies were selected for analysis, description, discussion and synthesis of the knowledge produced through them. After analysis, it was found that 94.6% of the studies were published in portuguese and 44.6% carried out in Northeast Brazil. In general, microbiological analyzes were performed using conventional methods (87.5%) and the most evaluated parameters were enumeration of thermotolerant coliforms (71.4%), research by Salmonella sp. (64.3%), enumeration of molds and yeasts (60.7%) and enumeration of total coliforms (58.9%). The studies that carried out the enumeration of thermotolerant coliforms, enumeration of molds and yeasts and research of Salmonella sp., 31.7%, 67.7% and 16.7%, respectively, presented at least one sample in disagreement with the permitted limits Brazilian law. The results of the evaluated studies demonstrated that the processing of fruit pulps in Brazil still faces problems of standardization regarding the required microbiological standards and limits considered safe for commercialization of this product. In this context, the need for greater vigilance and inspection of the processing of fruit pulps commercialized in the Brazilian territory is highlighted.